Electret integrated magnetic field sensor based on magnetostrictive polymer composite with nT resolution - Lukas Zimoch; Stefan Schröder; Eric Elzenheimer; Sören Kaps; Thomas Strunskus; Franz Faupel; Michael Höft; Rainer Adelung (Scientific Reports)
Abstract The pursuit for advanced magnetoelectric field sensors has gained momentum, driven by applications in various fields, ranging from biomedical applications to soft robotics and the automotive sector. In this context, a capacitive read-out based magnetostrictive polymer composite (MPC) sensor element is introduced, offering a new perspective on magnetic field detection. The sensor element’s unique feature is the possibility to independently tailor its mechanical and magnetic properties. When compared to other composite-based magnetic field sensors, the limit of detection (LoD) is three orders of magnitude lower (95.6 nT/√Hz at a resonance frequency of 160.5 Hz). In contrast to other electret-based ME sensors, the LoD is reduced by a factor of 20. To the best of the authors’ knowledge, this work marks the first comprehensive attempt to characterize a sensor magnetically, aligning with the thorough assessment standards of ME sensors. This study aims to narrow the disparity between established magnetic field sensors, featuring consistent characterization protocols, and the novel MPC sensors, which often undergo limited magnetic characterization as part of their evaluation. The presented sensor, built from readily available materials, offers a versatile and tuneable platform for magnetic field detection, and ongoing research aims to unlock its full potential in diverse applications.